SCIENTIFIC RATIONALE OF ECONOMIC SAFETY UNDER GLOBALIZATION CONDITIONS - Lutsyk , Yu.A. (The actual problems of regional economy development, 2018)
The article is aimed at scientific substantiation of problems of economic security in the conditions of globalization of relations. The evolution of the term of economic security and its main elements are considered. The interpretation of the term of economic security by different scholars is analyzed and the actual vision of the term is formulated. The origin of the term "globalization" is explored, since the formation of the system of economic security becomes relevant for domestic enterprises in modern conditions. The real and potential phenomena that threaten the economic security of Ukraine that threaten the functioning and development of the economic, social and political system, as well as the vital needs and interests of man, society and the state are determined. Further research should be aimed at developing measures and mechanisms for ensuring economic security in the face of globalization of relations.